Effect of Supplemental Lysine to Low Protein Diet on Production Performance, Egg Quality and Serum Biochemical Parameters of Gramapriya Laying Hens - , A.K. Panda; B. Sahoo (Indian Journal of Animal Nutrition, 2025)
The present study was conducted to evaluate the effect of supplemental lysine to low protein diet on egg production, egg quality and serum biochemical parameters of Gramapriya Laying hens. A basal diet based on maize-soybean meal-deoiled rice bran (14% CP, 0.60% lysine) was formulated, which was adequate in all essential amino acids except lysine. Subsequently, three test diets were formulated by supplementing synthetic lysine at 0.05, 0.10 and 0.15% to obtain 065, 070 and 0.75% lysine, respectively. Each diet was fed ad libtum to 5 replicates of 6 birds in each groups. A lighting regime of 16h was provided and all the layers were kept under uniform management conditions throughout the experimental period (32-44 wks). Increasing dietary level of lysine from 0.60 to 0.65% significantly increased egg production and egg mass, and improved feed conversion ratio. Higher levels of lysine (0.70 or 0.75%) in the diet did not result in further improvement in these parameters. Lowest albumen and highest yolk content in eggs were observed in the dietary group containing 0.60% lysine in the diet. Increasing the lysine levels in the diet to 0.70 or 0.75% significantly increased the albumen content and reduced the yolk content in the eggs of Gramapriya laying hens. It was intermediate in 0.65% lysine containing diet. The serum protein concentration increased marginally by increasing the lysine content of diets from 0.60 to 0.65%. Further increasing the level of lysine to 0.70%, significantly increased the serum protein concentration compared to 0.60% lysine. Considering the overall performance, It is concluded that 0.70% lysine in the diet containing 14% CP is adequate for Gramapriya laying hens.